CHILDREN’S ACCEPTABILITY OF MID DAY MEAL (MDM) SUPPLIED FROM CENTRALIZED KITCHEN - AKSHAYA PATRA IN MEDAK DISTRICT - SARAH KAMALA, NAGARAJ SWATHI, K.UMA DEVI, S.SUCHIRITHA DEVI and (The Journal of Research, PJTSAU, 2019)
Malnutrition adversely affects Universalization of Elementary Education (UEE). Even if a malnourished child does attend school, he/she finds it difficult to concentrate on and participate in the learning activities in school. To combat classroom hunger and promoting better learning, school meals has been realized as an important means of protecting children’s right to food. In November 2001, an interim order of the Supreme Court of India directed that cooked meals must be provided in all government and governmentaided primary schools by converting the provision of a midday meal into a legal entitlement for all school-going children.The Government of India introduced a revised Mid Day Meal Scheme (MDMS) in 2006, increasing the calorie content of the meal to 450k.calories (from 300k.calories) and protein to 12g (from 8-12g).